Child Abuse Diagnostic and Forensic Considerations (Springer International Publishing, 2018)
This book offers an interdisciplinary approach to child abuse providing a comprehensive overview of the topic. From fetal life to adolescence, various patterns of child abuse are described in 23 chapters with highlight on early diagnostic features and differential diagnoses. Data on psychological and domestic violence is also presented. Readers will improve their knowledge in the field of child abuse, helping to identify such situations at onset and subsequently prevent recurrences. This volume outlines and summarizes the main different judicial processes for child abuse around the world. The book also provides the unique angle and information from experts in France, who unlike other countries, are fully independent of all other parties i.e. judges, prosecutors and families, thus having a unique insight to the origin and context of the violence. Insight to their approach can lead to better prevention of abuse around the world. Written by a panel of authors including paediatricians, radiologists, forensic scientists, a judge, a magistrate and a psychologist, this book is of interest to professionals involved in pediatrics healthcare, students, medical doctors or nurses. Beyond the field of health, the book may also concern professionals of social and judicial areas who deal with child abuse. .